The Role and Limitations of the Village Secretary’s Authority in the Absence of a Village Head - Rachmawati, Meida; Susano, Adhi (Faculty of Law, Universitas Pekalongan, 2025)
This study discusses the role and limitations of the Village Secretary’s authority in filling the vacancy of the Village Head position, which has become a crucial issue in village governance. Although the Village Secretary is the highest structural official after the Village Head, regulations governing the delegation of authority during a vacancy are still minimal and not explicit. The study uses a normative and empirical approach by analyzing laws and regulations as well as field practices in several villages. The results of the study indicate that the appointment of an Acting Village Head (Plt) by the regional government is the only legal mechanism that can provide full legitimacy to the authority of the Village Head. Delegating authority to the Village Secretary without an official legal basis risks triggering legal, administrative, and social conflicts, as well as potential legal liability. Therefore, clear regulations and firm procedures are needed, along with the development of village officials, to ensure that village governance continues to function effectively and accountably during the transition period of the Village Head position